HTPN 078: an enhanced case management study to achieve viral suppression among viremic HIV-positive men who have sex with men in the United States. (1st February 2023) - Remien, Robert H.; Dacus, Jagadīśa-devaśrī; Farley, Jason E.; Hughes, James P.; Gamble, Theresa; Wang, Zhe (Zoe); Batey, D. Scott; Mayer, Kenneth H.; del Rio, Carlos; Balán, Iván C.; Irvin, Risha; Mitchell, Kate M.; et al.
Abstract : Objective(s): After identifying and recruiting men who have sex with men living with HIV and virally unsuppressed, this study attempted to enhance treatment and care via case management to increase the proportion who achieved viral suppression. Design: Participants were randomized into one of two study arms: standard of care (SOC) or enhanced case management (CM) intervention. Participants were followed for 12 months with quarterly study assessments, with blood collected for CD4 + cell count testing, HIV viral load testing (primary prespecified outcome), and plasma storage. Methods: Participants identified via respondent-driven sampling and direct recruitment and were invited to participate in the randomized controlled trial. The CM intervention provided a wide range of support services including, health education, clinical care coordination, medication adherence support, and social service assistance. The month-12 assessment included questions about healthcare utilization, stigma, substance use, and mental health. Results: Among the 144 participants virally unsuppressed at baseline, most had had a previous positive HIV test result; were Black, non-Hispanic, gay and bisexual men, aged 22–50. Among the 128 participants at the last study visit, 68 were virally suppressed, with no statistically significant difference between the CM and SOC arms (viral suppression 42% and 53%, respectively; adjusted odds ratio = 0.62 [ P = 0.15; 95% confidence interval: 0.32, 1.2]). Conclusions: Reaching targets of at least 90% sustained viral suppression among all people with HIV will likely require more than an individual-level CM approach that addresses barriers to optimal care and treatment at multiple levels.